The Spatial Patterns of Pacenan House in Sumberejo, Situbondo - Taufik Hidayat; Yusfan Adeputera Yusron; Susilo Kusdiwanggo (Publikasi Indonesia, 2024)
Pacenan house is a traditional house of the coastal area in Situbondo. The architectural style of Pacenan house is adapted from Tanean lanjhang traditional house. The spatial pattern of Pacenan house differs from that of Tanean Lanjhang, as Pacenan house only has